2009
DOI: 10.3748/wjg.15.2900
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of maximal-outer-diameter and maximal-mural-thickness in use of ultrasound for acute appendicitis in children

Abstract: The MOD and the MMT are reliable criteria to diagnose acute appendicitis in children. An MOD > 0.57 cm and an MMT > 0.22 cm are the optimal criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Very high CRP levels may have a relation with the appendicitis being gangrenous. (19). Similar to these studies, we found in our study a statistically meaningful relationship between acute appendicitis and appendix diameter longer than 5 mm.…”
Section: Discussionsupporting
confidence: 92%
“…Very high CRP levels may have a relation with the appendicitis being gangrenous. (19). Similar to these studies, we found in our study a statistically meaningful relationship between acute appendicitis and appendix diameter longer than 5 mm.…”
Section: Discussionsupporting
confidence: 92%
“…[2,[21][22][23] Chen et al [21] found that BUS had a sensitivity of 96.4% and a specificity of 67.6% for the diagnosis of appendicitis, compared to a sensitivity of 86.2% and a specificity of 37% based on surgeons' clinical judgment. However, the prevalence of appendicitis was 75% in their study and all physician sonographers had extensive BUS experience, reflecting a setting atypical for most EDs.…”
Section: Discussionmentioning
confidence: 99%
“…This is largely in line with the current radiology literature. Je et al [23] determined that the optimal appendix diameter and wall thickness cut-off value for diagnosis of pediatric appendicitis were 5.7 mm and 2.2 mm, respectively. In another study, Van Randen et al [24] found thickened a p p e n d i x ( > 6 m m ) , t r a n s d u c e r t e n d e r n e s s a n d periappendiceal fat infi ltration to be signifi cant variables predicting ultrasound diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The ACT diagnosis of acute appendicitis has usually been based on the visualization of an appendix .6 mm in maximal diameter, with contrast enhancement in the thickened appendiceal wall and/or pericecal inflammatory changes, or on the visualization of an abscess, with or without an appendicolith; 13 one study has described the imaging features of USG and ACT for negative appendectomies in children. 8 Taylor et al 14 concluded that isolated ACT findings of an appendicolith without an inflammatory sign or minimal fat stranding were not sufficient signs for the diagnosis of appendicitis. Trout et al 15 showed that nonvisualization of the appendix was not related to accurate diagnosis of appendicitis because the smaller volume of intra-abdominal fat in children may contribute to the relatively low rate of normal appendix detection at ACT.…”
Section: Discussionmentioning
confidence: 99%
“…Wall thickness was measured from the luminal surface to the serosal layer and was considered to be thickened if it measured .2.2 mm. 8 Lymphadenopathy was defined as an enlarged node measuring .8 mm at its smallest diameter. 9 …”
Section: Assessment Of Act Findingsmentioning
confidence: 99%